1991
DOI: 10.1007/bf01409409
|View full text |Cite
|
Sign up to set email alerts
|

Coronary drug project: Experience with niacin

Abstract: Niacin was one of the treatments compared in the Coronary Drug Project, a placebo-controlled, multicenter trial of lipid-lowering drugs in the secondary prevention of coronary heart disease. A total of 1119 men, aged 30-64 at entry, were randomized to niacin and 2789 to placebo by the end of recruitment in March 1969. Although side-effects interfered with adherence to the niacin regimen, it was the most effective agent in achieving cholesterol-lowering (10% overall); other agents in the trial were clofibrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 8 publications
0
31
0
2
Order By: Relevance
“…Niacin was one of the first lipid-altering drugs to demonstrate a reduction in CHD events in the Coronary Drug Project. 28 At present, niacin is identified as the most effective HDL-raising therapy. Although the mechanism by which niacin raises HDL is not well understood, the predominant hypothesis is that niacin inhibits the holoparticle uptake of HDL, resulting in delayed catabolism.…”
Section: Niacin Therapymentioning
confidence: 99%
“…Niacin was one of the first lipid-altering drugs to demonstrate a reduction in CHD events in the Coronary Drug Project. 28 At present, niacin is identified as the most effective HDL-raising therapy. Although the mechanism by which niacin raises HDL is not well understood, the predominant hypothesis is that niacin inhibits the holoparticle uptake of HDL, resulting in delayed catabolism.…”
Section: Niacin Therapymentioning
confidence: 99%
“…Nonetheless over a 10 year follow up there was a 27% reduction in major coronary events (p<0.05). Extended follow up of those alive at the end of the trial revealed 11% fewer deaths (p<0.01) in those on niacin [74]. Better tolerability can be achieved with extended release niacin [75].…”
Section: Niacin Monotherapymentioning
confidence: 73%
“…Furthermore, this relationship exists for all statins, whether fungal metabolites or synthetic derivatives. In addition, other lipid-altering drugs such as bile acid sequestrants [12], niacin [13], and fibrates [14] have been demonstrated to lower cardiovascular events to a degree similar to statin therapy when adjusted for cholesterol reduction.…”
Section: Statins Are the Cornerstone Of Ldl Cholesterol Reductionmentioning
confidence: 99%